2000
DOI: 10.1177/0092070300282008
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Extrinsic Product Cues on Consumers' Perceptions of Quality, Sacrifice, and Value

Abstract: The authors report the results of two experiments designed to test the effects of extrinsic cues—price, brand name, store name, and country of origin—on consumers’perceptions of quality, sacrifice, and value. The results of the experiments support hypothesized linkages between (a) each of the four experimentally manipulated extrinsic cues and perceived quality, (b) price and perceived sacrifice, (c) perceived quality and perceived value, and (d) perceived sacrifice and perceived value. The results also indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
479
2
17

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 625 publications
(514 citation statements)
references
References 38 publications
16
479
2
17
Order By: Relevance
“…For example, Chao (1993) found that significant interaction between country of origin and price in his study: when country of origin image was good, the effect of price on consumer's perceived quality is not significant; but when country of origin image was bad, there was close association between price and consumer's perceived quality. Differently, Teas and Agarwal (2000) did not find any significant interaction among country of origin and price, brand, or store name. They provided the possible explanation that they presented respondents clear brand and store name in the experiment, which tampered the "Halo effect" of country of origin.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…For example, Chao (1993) found that significant interaction between country of origin and price in his study: when country of origin image was good, the effect of price on consumer's perceived quality is not significant; but when country of origin image was bad, there was close association between price and consumer's perceived quality. Differently, Teas and Agarwal (2000) did not find any significant interaction among country of origin and price, brand, or store name. They provided the possible explanation that they presented respondents clear brand and store name in the experiment, which tampered the "Halo effect" of country of origin.…”
Section: Discussioncontrasting
confidence: 61%
“…As an extending of Dodds et al's research, Teas and Agarwal (2000) explored the effect of price, brand name, store name, and country of origin on perceived quality, perceived sacrifice, and perceived value. They found even other three extrinsic cues-brand name, store name, and country of origin were available, there was a significant positive relationship between price and perceived quality.…”
Section: Hypothesesmentioning
confidence: 99%
“…The purchase decision depends on consumer perceived sacrifice to obtain the product, which includes product price (TEAS and AGARWAL, 2000). We observed significant difference between the prices of welfare-friendly and regular products (Table 1).…”
Section: Product Availabilitymentioning
confidence: 90%
“…The latter is the primary focus of this paper. The impact of place brand on quality perceptions has been shown to be virtually identical to that of brand name ( Teas and Agarwal, 2000) . Place brands are a combination of the sourced factor and the source place.…”
Section: Overview Of Place Brandsmentioning
confidence: 90%